Brief exposure to directionally-specific pulsed electromagnetic fields stimulates extracellular vesicle release and is antagonized by streptomycin: A potential regenerative medicine and food industry paradigm. (August 2022) - Wong, Craig Jun Kit; Tai, Yee Kit; Yap, Jasmine Lye Yee; Fong, Charlene Hui Hua; Loo, Larry Sai Weng; Kukumberg, Marek; Fröhlich, Jürg; Zhang, Sitong; Li, Jing Ze; Wang, Jiong-Wei; Rufaihah, Abdul Jalil; Franco-Obregón, Alfredo
Abstract: Pulsing electromagnetic fields (PEMFs) have been shown to promote in vitro and in vivo myogeneses via mitohormetic survival adaptations of which secretome activation is a key component. A single 10-min exposure of donor myoblast cultures to 1.5 mT amplitude PEMFs produced a conditioned media (pCM) capable of enhancing the myogenesis of recipient cultures to a similar degree as direct magnetic exposure. Downwardly-directed magnetic fields produced greater secretome responses than upwardly-directed fields in adherent and fluid-suspended myoblasts. The suspension paradigm allowed for the rapid concentrating of secreted factors, particularly of extracellular vesicles. The brief conditioning of basal media from magnetically-stimulated myoblasts was capable of conferring myoblast survival to a greater degree than basal media supplemented with fetal bovine serum (5%). Downward-directed magnetic fields, applied directly to cells or in the form of pCM, upregulated the protein expression of TRPC channels, markers for cell cycle progression and myogenesis. Direct magnetic exposure produced mild oxidative stress, whereas pCM provision did not, providing a survival advantage on recipient cells. Streptomycin, a TRP channel antagonist, precluded the production of a myogenic pCM. We present a methodology employing a brief and non-invasive PEMF-exposure paradigm to effectively stimulate secretome production and release for commercial or clinical exploitation.